Pengaruh Penilaian Prestasi Kerja, Promosi Jabatan Dan Kompetensi Pegawai Terhadap Pengembangan Karir Aparatur Sipil Negara (ASN) Pada Dinas Perindustrian Kota Medan - Laila Ali Marpaung; Yahya Tanjung (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
The purpose of this study was to determine the effect of Job Performance Assessment, Promotion and Employee Competence on Career Development of State Civil Apparatus at the Medan City Industry Service office, either partially or simultaneously. The type of this research was a descriptive quantitative research used Multivariate Linear Regression Analysis method. Population in this study amounted to 52 employees and the sample for this study also amounted to 52 employees, so that the sampling technique used the Saturated Sampling Technique. Instrument test of this study used Likert Scale and data processing in this study used the Statistical Program for Social Science software program version 25. Result showed that as partially, the Job Performance Assessment had a negative and significant effect on Career Development of State Civil Apparatus with t-count value of -3.366 and significant value of 0.00 smaller than alpha value of 0.05. Promotion had a negative and significant effect on Career Development of State Civil Apparatus with t-count value of -4.348 and significant value of 0.000 smaller than alpha value of 0.05. Employee Competence had a positive and significant effect on Career Development of State Civil Apparatus with t-count value of 3.511 and significant value of 0.001 smaller than alpha value of 0.05. Simultaneously, Job Performance Assessment, Promotion and Employee Competence had Positive and significant effects on Career Development of State Civil Apparatus with F-count value of 8.027 and significant value of 0.000 smaller than alpha value of 0.05. Based on the results of the R2 Determination test, it was known that the Adjusted R value is 0.292, which meant that the contribution of the influence was given by the three independent variables to the dependent variable was 29.2%, the remaining 70.8% was influenced by other variables not examined in this study.